Pakistan: The Army’s Growing Political Role - Shah, Barkha (2016)
THE CARNAGE in Pakistan on the weekend of May 12 and 13 was extremely perturbing. The most worrisome was the situation in Karachi, which saw its worst bloodshed in two decades. Since the unconstitutional ousting of the Chief Justice of Pakistan by the President, General Pervez Musharraf, the country has been engulfed in political turmoil. Opposition parties, already discontent with the political situation, have jumped on the opportunity and are offering support to the former Chief Justice by mobilising against the government. The former CJ has been traveling around the country, and has been welcomed enthusiastically by rallies launched by the opposition parties.